Aktivitas Antiseptik Lotion Kombinasi Ekstrak Herbal Pegagan (Centella Asiatica (L.) Urban Dan Aloe Vera Terhadap Bakteri Pseudomonas Aeruginosa - Delladari Mayefis; Rury Trisa Utami (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Pseudomonas aeruginosa is a bacterium that can cause a variety of diseases, one of which is an infection with the skin. Where one of the ways to prevent infections of the skin is by hand washing, one of them uses antiseptic. The study aims to test the antibacterial ativity of the gel antiseptic, a combination of Centella Asiatica extract and aloe vera extract against Pseudomonas aeruginosabacteria. This research uses a method of diffuse diffusion with the concentration of a combination of Centella asiatica and Aloe vera extract is 5%: 5% (f IV), 7.5%: 2.5% (f V), 7.5%: 2.5% (f VI), with positive control using an antiseptic antic. Antibacterial activity with an antiseptic combination of Centella Asiatica herbal extract and aloe vera against Pseudomonas aeruginosa bacteria has a moderate-to-medium catfisher inhibition of 18.06 mm. Based on statistical tests using ANOVA indicates there is a significant difference between the average percentage value between groups (sig ≤ 0.05).